Social Work Educators’ Perceptions of School Social Work Leadership – What are the Characteristics that Make a Leader? - Christine Vyshedsky (International Journal of School Social Work, 2023)
Social workers in school settings are uniquely poised to propose and implement proactive solutions to climate stressors, but they may not capitalize on this opportunity to lead. This study explored the perceptions of Masters’ level social work educators, who set the tone and expectations for school social workers through curricula, towards the inclusion of leadership-related skills within school social work curriculum. A survey of educator administrators (n = 75) at Council on Social Work Education (CSWE) accredited institutions examined leadership as defined through a combination of two proposed definitions for social work leadership, delineated by Holosko, 2009 and Hopson & Lawson, 2011; findings revealed no relationship between the perceived importance of the inclusion of social work leadership skills and any components of leadership except for the ability for school social workers to collaborate. Results support a need for further exploration and definition of leadership in school social work, with the aim of empowering practitioners and reducing role ambiguity.
Keywords: School social work; leadership; masters education; curricula; curriculum; collaborative leadership